2022
DOI: 10.3389/fcimb.2022.943735
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of uncommon KL38-OCL6-ST220 carbapenem-resistant Acinetobacter pittii strain, co-producing chromosomal NDM-1 and OXA-820 carbapenemases

Abstract: ObjectiveTo characterize one KL38-OCL6-ST220 carbapenem-resistant Acinetobacter pittii strain, co-producing chromosomal NDM-1 and OXA-820 carbapenemases.MethodsA. pittii TCM strain was isolated from a bloodstream infection (BSI). Antimicrobial susceptibility tests were conducted via disc diffusion and broth microdilution. Stability experiments of blaNDM-1 and blaOXA-820 carbapenemase genes were further performed. Whole-genome sequencing (WGS) was performed on the Illumina and Oxford Nanopore platforms. Multilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Virulence factors were predicted using ABRicate (139,140) v1.0.1 (https://github.com/tseemann/ABRicate). The default virulence factor database included in ABRicate was replaced with DNA sequences from the full dataset to include all genes related to known and predicted virulence factors (141), (http://www.mgc.ac.cn/VFs/download.html).…”
Section: Methodsmentioning
confidence: 99%
“…Virulence factors were predicted using ABRicate (139,140) v1.0.1 (https://github.com/tseemann/ABRicate). The default virulence factor database included in ABRicate was replaced with DNA sequences from the full dataset to include all genes related to known and predicted virulence factors (141), (http://www.mgc.ac.cn/VFs/download.html).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to A. baumannii , few studies have focused on A. nosocomialis and A. pittii in recent decades owing to their lower prevalence and resistance rates. However, they have garnered increasing research attention recently owing to a rise in antibiotic resistance and changes in resistance mechanisms, particularly in A. pittii strains ( Singkham-In and Chatsuwan, 2018 ; Chen et al., 2019 ; Zhang et al., 2020 ; Yang et al., 2021 ; Ding et al., 2022 ; Tian et al., 2022 ). Additionally, a recent multicenter investigation in Japan indicated that A. pittii is the most significant species responsible for invasive Acinetobacter infections ( Kiyasu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 12 Closely related plasmids were predicted using the Bacterial Isolate Genome Sequence Database (BIGSdb). 13 …”
mentioning
confidence: 99%